Majorization Properties for Certain Subclasses of Meromorphic Function of Complex Order - Neelam Khan; Muhammad Arif; Maslina Darus (Complexity)
By making use of q−differential operators, many distinct subclasses of analytic and meromorphic functions have already been defined and investigated from numerous perspectives. In this article, we investigated several majorization results for the class of meromorphic univalent functions of complex order, defined by q−differential operator. Moreover, we pointed out some new or known consequences of our results, which is in the form of corollaries.